Probing the active site of cinnamoyl CoA reductase 1 (Ll-CCRH1) from Leucaena leucocephala - Sonawane, Prashant; Patel, Krunal; Vishwakarma, Rishi Kishore; Srivastava, Sameer; Singh, Somesh; Gaikwad, Sushama M.; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2013)
Lack of three dimensional crystal structure of cinnamoyl CoA reductase (CCR) limits its detailed active site characterization studies. Putative active site residues involved in the substrate/NADPH binding and catalysis for Leucaena leucocephala CCR (Ll-CCRH1; GenBank: DQ986907) were identified by amino acid sequence alignment and homology modeling. Putative active site residues and proximal H215 were subjected for site directed mutagenesis, and mutated enzymes were expressed, purified and assayed to confirm their functional roles. Mutagenesis of S136, Y170 and K174 showed complete loss of activity, indicating their pivotal roles in catalysis. Mutant S212G exhibited the catalytic efficiencies less than 10% of wild type, showing its indirect involvement in substrate binding or catalysis. R51G, D77G, F30V and I31N double mutants showed significant changes in K-m values, specifying their roles in substrate binding. Finally, chemical modification and substrate protection studies corroborated the presence Ser, Tyr, Lys, Arg and carboxylate group at the active site of Ll-CCRH1. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Chemical modification; Cinnamoyl CoA reductase 1; Docking simulations; homology modeling; Site directed mutagenesis; Substrate protection